2020
DOI: 10.1111/jth.15033
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world evidence on the use of benzodiazepine receptor agonists and the risk of venous thromboembolism

Abstract: Venous thromboembolism (VTE) typically presents as deep vein thrombosis of the lower limbs and can result in pulmonary embolism, a potential cause of mortality. 1 Known risk factors for VTE include advancing age, immobilization, cancer, trauma, pregnancy, and estrogen-related medications. 2 The use of benzodiazepine receptor agonist (BZRA) is increasing in many countries, 3,4 with a 1-year prevalence of 5.2% for adults in the United States 5 and 22.2% in Taiwan. 6 BZRAs produce sedative,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Particularly, the number of benzodiazepine receptor agonists (BZRAs) prescriptions is high among hypnotics and anxiolytics in Japan [ 2 ]. Also, many studies reported adverse effects of BZRAs, such as falls and venous thromboembolism [ 3 , 4 ]. However, in recent years, hypnotics and anxiolytics or BZRAs prescription trends have not been revealed using nationwide statistics data.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the number of benzodiazepine receptor agonists (BZRAs) prescriptions is high among hypnotics and anxiolytics in Japan [ 2 ]. Also, many studies reported adverse effects of BZRAs, such as falls and venous thromboembolism [ 3 , 4 ]. However, in recent years, hypnotics and anxiolytics or BZRAs prescription trends have not been revealed using nationwide statistics data.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to antipsychotics, several benzodiazepines had a positive, previously reported association. 43 Immobilization and sedation may be potential contributors to the thrombosis risk. All in all, thrombotic risk among patients with severe psychiatric disorders and psychotropic medications is important in clinical practice, and the threshold of adequate diagnostics should be low in cases of potential thrombotic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that BZD receptor agonists significantly increase odds of venous thromboembolism (VTE), with BZD hypnotics having higher odds of VTE. 13 Our study sought to add to the existing literature on immunosuppressive effects and thrombotic complications of BZDs, as it relates to trauma patients. Specifically, we sought to determine if rates of infectious or thrombotic complications among trauma patients were higher in those who tested positive for BZDs on admission.…”
mentioning
confidence: 99%
“…Thomassen et al 12 conducted a study that demonstrated that, out of the psychotropic drugs analyzed (antipsychotics, antidepressants, and BZDs), BZDs had the highest odds ratio of developing deep vein thrombosis (DVT). In addition, it has been shown that BZD receptor agonists significantly increase odds of venous thromboembolism (VTE), with BZD hypnotics having higher odds of VTE 13 …”
mentioning
confidence: 99%